Light-induced Hydrogen Sulfide Release from “Caged” gem-Dithiols - Devarie-Baez, Nelmi O. (2013)
[Image: see text] “Caged” gem-dithiol derivatives that release H(2)S upon light stimulation have been developed. This new class of H(2)S-donors was proven, by various spectroscopic methods, to generate H(2)S in an aqueous/organic medium as well as in cell culture.